Air-blood barrier thickening and alterations of alveolar epithelial type 2 cells in mouse lungs with disrupted hepcidin/ferroportin regulatory system - Mühlfeld, Christian Axel; Neves, Joana; Altamura, Sandro; Muckenthaler, Martina (Histochemistry and cell biology, 2019)
Iron accumulates in the lungs of patients with common respiratory diseases or transfusion-dependent beta-thalassemia. Based on our previous work, we hypothesized that systemic iron overload affects the alveolar region of the lung and in particular the surfactant producing alveolar epithelial type II (AE2) cells. Mice with a point mutation in the iron exporter ferroportin, a model for human hemochromatosis type 4 were compared to wildtype mice (n = 5 each). Lungs were fixed and prepared for light and electron microscopy (EM) according to state-of-the-art protocols to detect subcellular iron localization by scanning EM/EDX and to perform design-based stereology. Iron was detected as electron dense particles in membrane-bound organelles, likely lysosomes, in AE1 cells. AE2 cells were higher in number but had a lower mean volume in mutated mice. Lamellar body volume per AE2 cell was lower but total volume of lamellar bodies in the lung was comparable to wildtype mice. While the volume of alveoli was lower in mutated mice, the volume of alveolar ducts as well as the surface area, volume and the mean thickness and composition of the septa was similar in both genotypes. The thickness of the air-blood barrier was greater in the mutated than in the WT mice. In conclusion, disruption of systemic iron homeostasis affects the ultrastructure of interalveolar septa which is characterized by membrane-bound iron storage in AE1 cells, thickening of the air-blood barrier and hyperplasia and hypotrophy of AE2 cells despite normal total intracellular surfactant pools. The functional relevance of these findings requires further analysis to better understand the impact of iron on intra-alveolar surfactant function.
Published online: 3 October 2018
Gesehen am 15.05.2019